The persepsi publik terhadap identitas transgender sebagai 'the other' di sosial media - Vany Fitria; Desika Putri Mardiani; Abdulsalam Aderibigbe (Jurnal Riset Komunikasi (JURKOM), 2024)
Waria also known as transgender women, despite consistent exclusion from society, are becoming increasingly visible in Indonesia during the era of globalization. In recent years, they have gained more popularity by leveraging the rapid development of social media. This study aims to critically examine public perceptions of transgender, using the case of one of Indonesia's most famous transgender figures, Lucinta Luna. The researcher analyses Instagram users’ comments on her account, as a representation of how the public responds to Luna's identity as a transgender. This study utilizes a qualitative approach and thematic analysis as the analytical method. To analyze the data, this research uses Computer-Aided Qualitative Analysis Software (CAQDAS) NVivo 12. Furthermore, this study adopts Hall's theory of 'the other' to critically examine how Indonesians respond to transgenders. This research found that two significant themes emerged from overall Instagram users' comments on Luna's identity, which are negative and positive public perceptions. In both themes, three sub-themes emerged: sarcasm, religious criticism, and sexual harassment in the negative theme, and admiration, comedy, and a supportive attitude in the positive theme.